The Effectiveness of Training Methods in Improving The Knowledge of PKK Members and Health Cadres Regarding The Prevention of Conjunctivitis Transmission In Malang - Ariq Fadhil Athallah; Ovi Sovia; Hera Dwi Novita (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2023)
Conjunctivitis is one of the frequent causes of red eyes, this condition is an infection of the mucous membrane of the eye or conjunctiva. According to data from the Indonesian Health Profile 2009 and 2010, conjunctivitis and other conjunctival disorders are among the top 10 most common diseases in hospital outpatients. The high number is caused by conjunctivitis outbreaks that can occur at any time of the year. The solution that can be done to overcome these problems is to increase public knowledge related to the prevention of conjunctivitis disease transmission through cooperation with PKK mothers and health cadres who act as educators in their environment with direct training. Based on these considerations, this study aims to determine the effectiveness of using training methods to improve the knowledge of PKK mothers and health cadres in Malang City about conjunctivitis. This study aims to examine the effectiveness of the training method in increasing the knowledge of Family Welfare Empowerment (PKK) mothers and health cadres related to the prevention of conjunctivitis transmission in Malang City. The study used a pre-experimental research design with a pre-test and post-test design with control group with purpose random sampling technique. Based on the research, there was a significant increase in the number of participants who experienced an increase in scores (n>70%) which stated the effectiveness of using training methods to increase the knowledge of PKK mothers and Health Cadres in Malang city related to conjunctivitis.